Design a Heart Rate Counter Based on the Atmega328 Microcontroller Displayed Via Smartpone - Pratama, Gilang Ariya; Yudhana, Anton (Signal and Image Processing Letters, 2021)
In today's era, technological advances are experiencing a rapid impact on human life as well as smartphones that trigger and influence technological developments in the health sector. The process of monitoring human heart rate can be known by its pulse that can be done by everyone by utilizing technological developments. The purpose of this study was to determine the design of a pulse response detection research test kit with a heartbeat sensor and display data through a smartphone. Using a pulse heart sensor attached to one person's fingertip to detect the pulse rate signal, then the sensor reading data is received by the smartphone via an analog pin (AO), forwarded via Bluetooth and displayed on the serial monitor application in the smartphone, then it will be processed into BPM (beats per minute) so that it can find out the pulse ticking signal displayed on the smartphone. Based on the results of the simulation carried out, the results of testing the tool on the heart rate sensor were able to detect the pulse rate signal response. A person's pulse rate when doing sports activities beats quickly compared to the pulse before doing sports activities, because when doing sports activities the heartbeat pumps blood to all parts of the body quickly. After testing, the tool can detect the number of pulses a person can work normally ranging from 90 to 100 Beat Per Minute (BPM) and indicates that the tool can work properly.